IgA Nephropathy After SARS-CoV-2 Vaccination - Matthew Abramson; Samuel Mon-Wei Yu; Kirk N. Campbell; Miriam Chung; Fadi Salem (Kidney Medicine, 2021)
Here we present the first case of newly diagnosed IgA nephropathy (IgAN) after a SARS-CoV-2 vaccination. A 30-year-old man with no known past medical history presented with gross hematuria and subnephrotic proteinuria 24 hours after the second dose of the mRNA-1273 SARS-CoV-2 vaccine. A kidney biopsy showed IgAN. He was started on an angiotensin receptor blocker, resulting in proteinuria reduction. Similar to natural infection of SARS-CoV-2, persons who receive 2 mRNA-based vaccines demonstrate robust antibodies against the receptor-binding domain (RBD) of the S1 protein. Given the uniqueness of glycosylation of RBD and potent stimulation of immune response from mRNA-based vaccine compared to other vaccines, we hypothesize that our patient developed de novo antibodies, leading to IgA-containing immune-complex deposits. This case highlights the urgency of understanding the immunological responses to novel mRNA-based SARS-CoV-2 vaccines in more diverse populations. Despite the lack of clear causality, nephrologists should be alerted if any new-onset hematuria or proteinuria is observed.